2013
DOI: 10.1107/s1600536813001086
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorido(2,9-dimethyl-1,10-phenanthroline-κ2N,N′)mercury(II)

Abstract: The title compound, [HgCl2(C14H12N2)], consists of one 2,9-dimethyl-1,10-phenanthroline (dmphen) ligand chelating the HgII ion and two chloride ligands coordinating to the HgII ion, forming a distorted tetra­hedral environment. The dmphen ligand is nearly planar (r.m.s. deviation = 0.0225 Å). The dihedral angle between the normal to the plane defined by the HgII atom and the two Cl atoms and the normal to the plane of the dmphen ring is 81.8 (1)°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The DMP complexes with zinc (Zn-DMP), manganese (Mn-DMP), iron (Fe-DMP), cobalt (Co-DMP), nickel (Ni-DMP), copper (Cu-DMP), cadmium (Cd-DMP), mercury (Hg-DMP), and lead (Pb-DMP) were synthesized as described previously (Wang, 2009;Preston et al, 1968;Shen and Lush, 2010;Torbati et al, 2010;Das et al, 2013;Guo et al, 2009;Xia et al, 2011;Davies and Loose, 1976;Warad et al, 2011;Warad et al, 2013;Morsali et al, 2004;Hara et al, 2016) with some modifications, and identified by the element analysis.…”
Section: Synthesis Of Dmp Complexesmentioning
confidence: 99%
“…The DMP complexes with zinc (Zn-DMP), manganese (Mn-DMP), iron (Fe-DMP), cobalt (Co-DMP), nickel (Ni-DMP), copper (Cu-DMP), cadmium (Cd-DMP), mercury (Hg-DMP), and lead (Pb-DMP) were synthesized as described previously (Wang, 2009;Preston et al, 1968;Shen and Lush, 2010;Torbati et al, 2010;Das et al, 2013;Guo et al, 2009;Xia et al, 2011;Davies and Loose, 1976;Warad et al, 2011;Warad et al, 2013;Morsali et al, 2004;Hara et al, 2016) with some modifications, and identified by the element analysis.…”
Section: Synthesis Of Dmp Complexesmentioning
confidence: 99%
“…8d, an interplanar distance of 3.360(9) Å, an intercentroid distance of 3.605(9) Å and a displacement of 3.682(8) Å). The chloride and bromide complexes show a more opened crystal packing and a herringbone pattern, 23,24 while in the iodide derivative and in 5, the ligands are disposed on parallel planes.…”
Section: Crystalline Structuresmentioning
confidence: 99%
“…1). Mononuclear [Hg(L) X 2 ] complexes with these ligands have been reported [18][19][20][21][22][23][24][25][26][27] and complexes [Hg( phen)Br 2 ] (9) and [Hg(terpy)Br 2 ] (10) have been synthesised and characterized in this work. The use of the bpym ligand resulted in the formation of coordination polymers, as previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a series of several mixed-ligand mononuclear [ 27 , 28 ] and dinuclear [ 29 , 30 ] metal complexes have a general formula MX 2 (dmphen) (2,9-dimethyl-1,10-phenanthroline, X = Cl, NCS) prepared in our lab. These complexes were found to be suitable precursors for spherical shape metal oxide nanoparticles [ 31 ].…”
Section: Introductionmentioning
confidence: 99%